The Palgrave Handbook of Education Law for Schools (Springer International Publishing, 2018)
This Handbook examines the essential nature of the law within an educational context and asks why there is not greater preparation for this aspect of a teacher's role. Principals and teachers across the world now work in increasingly uncertain and challenging environments involving complex legislative frameworks, with their roles and responsibilities constantly changing to meet these demands: thus, it is imperative that educators adapt and acquire new skills relating to child protection and criminal law. On a daily basis, teachers and practitioners are being challenged to critically examine and evaluate the legal rights and obligations of various stakeholders, including students, parents, educators and administrators. However, if these skills are not developed, the implications will be significant: particularly so if principals are deterred from pursuing innovative education strategies due to potential litigation risks. Consequently, the chapters will empower principals and teachers in the management of these concerns. This wide-ranging handbook, including case studies from around the world, will be of interest and value to both scholars of education law and practitioners. .